Most important algebra questions asked in SSC CGL

In this article , some  important algebra  questions asked in SSC CGL previous year papers  are  discussed with explanations.

1. If x+\frac{1}{x}=\sqrt{2}

  then find

(i) x^{16}+x^{12}+x^{8}+x^{4}+1

(ii) x^{60}+\frac{1}{x^{60}}

(iii) x^{61}+\frac{1}{x^{61}}

(iv) x^{99}+x^{95}+1

Sol.   Given x+\frac{1}{x}=\sqrt{2}  .

Squaring both sides  we get,  x^{2}+\frac{1}{x^{2}}+2=2

\Rightarrow x^{2}+\frac{1}{x^{2}}=0

\Rightarrow x^{4}+1=0. Hence x^{4}=-1

(i)  Now x^{16}+x^{12}+x^{8}+x^{4}+1= (x^{4})^{4}+ (x^{4})^{3}+(x^{4})^{2}+x^{4}+1

Putting   x^{4}=-1  , we get

x^{16}+x^{12}+x^{8}+x^{4}+1 =   (-1)^{4}+(-1)^{3}+(-1)^{2}+(-1)+1


(ii) x^{60}+\frac{1}{x^{60}}=(x^{4})^{15}+\frac{1}{(x^{4})^{15}}=(-1)^{15}+\frac{1}{(-1)^{15}}=-1-1=-2

(iii) x^{61}+\frac{1}{x^{61}}= x^{60}\times x+\frac{1}{x^{60}\times x} = (x^{4})^{15}\times x+\frac{1}{(x^{4})^{15}\times x}

= (-1)^{15}\times x+ \frac{1}{(-1)^{15}\times x}=-x-\frac{1}{x}=-(x+\frac{1}{x})=-\sqrt{2}

(iv) x^{99}+x^{95}+1= x^{95}(x^{4}+1)+1=(x)^{95}(-1+1)+1= x^{95}\times 0+1=1

2.   If x+\frac{1}{x}=5 , then find the value of x^{3}+\frac{1}{x^{3}} .

Sol.  Cubing both the sides , we get  (x+\frac{1}{x})^{3}=125

\Rightarrow x^{3}+\frac{1}{x^{3}}+3\times x\times \frac{1}{x}(x+\frac{1}{x})=125           [\because  (a+b)^{3}=a^{3}+b^{3}+3ab(a+b)  ]

\Rightarrow x^{3}+\frac{1}{x^{3}}+3\times 5=125                   [ putting the value of x+\frac{1}{x} ]

\Rightarrow  x^{3}+\frac{1}{x^{3}}=125-15.     Hence x^{3}+\frac{1}{x^{3}}=110


We can use the following formula directly  \bg_green \bg_green x+\frac{1}{x} =k , \, \, \, then\, \, \, \, \, x^{3}+\frac{1}{x^{3}}=k^{3}-3k

3. If x^{4}+\frac{1}{x^{4}}=194, x>0,    then  find   the value of  \left ( x-2 \right )^{2} .

Sol.  Given x^{4}+\frac{1}{x^{4}}=194

Adding 2 both sides we get x^{4}+\frac{1}{x^{4}}+2=194+2=196  . It  can be written as

\left ( x^{2} +\frac{1}{x^{2}}\right )^{2}=\left ( 14 \right )^{2}

Taking +ve square root of both sides, we get x^{2}+\frac{1}{x^{2}}=14

Again adding 2 both the sides we get  x^{2}+\frac{1}{x^{2}}+2=14+2=16

This implies    (x+\frac{1}{x})^{2}=4^{2}. Hence x+\frac{1}{x}=4 \, \, \, \, .......(i)

Now \left ( x-2 \right )^{2}=x^{^{2}}+4-4x =4x-1+4-4x=3   ( from equ. (i) x^{2}+1=4x)

Thus (x-2)^{2}=3

4. If  x^{99}+\frac{1}{x^{99}}=11   then find the value of x^{99}-\frac{1}{x^{99}}  .

Sol.  To solve the above question you  can use the following formula

(i ) If x^{n}+\frac{1}{x^{n}}=k then x^{n}-\frac{1}{x^{n}}=\sqrt{k^{2}-4}    and

(ii) If x^{n}-\frac{1}{x^{n}}=k  then x^{n}+\frac{1}{x^{n}}=\sqrt{k^{2}+4}

Proof. (i ) Given x^{n}+\frac{1}{x^{n}}=k

Squaring both sides we get x^{2n}+\frac{1}{x^{2n}}+2=k^{2}

\Rightarrow x^{2n}+\frac{1}{x^{2n}}=k^{2}-2.  Now subtracting 2 from both sides we get,  x^{2n}+\frac{1}{x^{2n}}-2=k^{2}-4

\Rightarrow (x^{n}-\frac{1}{x^{n}})^{2}=k^{2}-4

\Rightarrow x^{n}-\frac{1}{x^{n}}=\sqrt{k^{2}-4}

Similarly we can prove that  If x^{n}-\frac{1}{x^{n}}=k  then x^{n}+\frac{1}{x^{n}}=\sqrt{k^{2}+4}

Now using the above formula the value of  x^{99}-\frac{1}{x^{99}}   =\sqrt{11^{2}-4}=\sqrt{117}  .

5. If x^{2}-2\sqrt{5}\, x+1=0  , then find the value of x^{5}+\frac{1}{x^{5}}.

Sol.  Dividing the given equation by x, we get  x-2\sqrt{5}+\frac{1}{x}=0.  This implies  x+\frac{1}{x}=2\sqrt{5}  ………… (i)

On squaring both sides we get, (x+\frac{1}{x})^{2}=20. It gives x^{2}+\frac{1}{x^{2}}=20-2=18     ………………. (ii)

Now cubing both sides  of eqiuation (i), we get  x^{3}+\frac{1}{x^{3}}+3 \times x\times \frac{1}{x}(x+\frac{1}{x})=40\sqrt{5} . This implies x^{3}+\frac{1}{x^{3}}=40\sqrt{5}-6\sqrt{5}=36\sqrt{5}     …………….(iii)

squaring equation (ii) we get  x^{4}+\frac{1}{x^{4}}=(18)^{2}-2= 324-2=322    …………..(iv)

Now (x^{4}+\frac{1}{x^{4}})(x+\frac{1}{x})=322\times 2\sqrt{5} . This gives  x^{5}+x^{3}+\frac{1}{x^{3}}+\frac{1}{x^{5}}=644\sqrt{5}  . Thus


On putting the value of x^{3}+\frac{1}{x^{3}} from (iii),   the value of  x^{5}+\frac{1}{x^{5}}=644\sqrt{5}-34\sqrt{5}=610\sqrt{5}

6. If 30x^{2}-15x+1=0, then what is the value of 25x^{2}+\frac{1}{36x^{2}} .

Sol.   Given that  30x^{2}-15x+1=0 .

Dividing by 6x, we get 5x-\frac{15}{6}+\frac{1}{6x}=0 \Rightarrow 5x+\frac{1}{6x}=\frac{15}{6}. Now squaring both sides we get

25x^{2}+\frac{1}{36x^{2}}+2\times 5\times \frac{1}{6}=\frac{225}{36 }.     This implies  25x^{2}+\frac{1}{36x^{2}}=\frac{225}{36}-\frac{10}{6}=\frac{165}{36}=\frac{55}{12} .


Leave a Reply

Your email address will not be published.

IBPS Clerk Exam Date 2022 Out SSC MTS Admit Card 2022 Government Exam Calendar July 2022 CBSE Class 11 Mathematics Revised Syllabus 2022-2023 UGC NET 2022 Exam Date